(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Software designed to automate the payroll process is called a payroll system. These systems are used to keep track of employee working hours, calculate salaries, calculate taxes and deductions, print payslips, and more. They can be integrated with leave and attendance tracking systems and the employee self-service portal. The developed system can monitor or oversee everything having to do with the most common way of paying workers and recording business charges. They are put in place to calculate wages, withhold taxes, and other deductions, print and deliver checks, and pay employment taxes to the government. Most of the parts of the payroll management system are currently functional and ready for implementation, and the other parts remain prototyped and need to be finalized by an IT Specialist. The following discussion based on the developed payroll management system states that the researchers solve the following problems: Monitoring Attendance, Inaccurate Information, Disputes on Salary, and Pay slips that we provide to each employee. The Payroll System for Attendance Monitoring is a system where the daily records of each employee are recorded. After testing, it was found that the technology used was compatible with Structured Query Language (SQL)). It successfully runs the payroll system, including the personal information of the employees and the mandatory government contributions.